SOSIALISASI PENDAMPINGAN PEMBUATAN BAHAN AJAR MENGGUNAKAN ARTIFICIAL INTELLIGENCE DI SMP MUHAMMADIYAH 07 SUKARAJA KECAMATAN BUAY MADANG KABUPATEN OKU TIMUR - Anam, Syaiful; Saputri, Levia; Lestari, Silvya Anggun (Fakultas Pertanian, 2024)
The application of artificial intelligence (AI) in education has great potential to improve the quality of learning. This community service aims to socialise and train teachers at SMP Muhammadiyah 07 Sukaraja in making AI-based teaching materials. The method in this service goes through several stages, namely 1) Preparation and Planning, 2) Socialisation and Training, 3) Implementation and Assistance. As a result of this service activity, it is hoped that teachers can utilise AI technology to create teaching materials that are more interactive and effective, so as to increase student motivation and learning outcomes